COUNTRY OF ORIGIN, BRAND IMAGE AND HIGH INVOLVEMENT PRODUCT TOWARDS CUSTOMER PURCHASE INTENTION: EMPIRICAL EVIDENCE OF EAST MALAYSIAN CONSUMER - Mohd Amirul Adenan; Jati Kasuma Ali; Dayang Humida Abang Abdul Rahman (Jurnal Manajemen dan Kewirausahaan, 2018)
This research strives to understand East Malaysian consumers’ purchase intention when being exposed to the effects of brand image and country of origin (COO) image in the case of high involvement products. Self-administered questionnaires were collected from 225 consumers in East Malaysia. The result of this study shows that East Malaysian consumers’ put a large importance on brand and country of origin image in high involvement products as they are more involved in information searching and decision making when purchases these products. Implication and future research also discussed.